Variability in the Perception of Informed Consent for IV-tPA during TeleStroke Consultation - Lisa Elizabeth Thomas (Frontiers in Neurology, 2012)
OBJECTIVE: To study the perception of informed consent among various raters for thrombolysis in acute ischemic stroke patients receiving IV-tPA.METHODS: Twenty randomly selected videotaped telestroke consultations of acute stroke patients administered IV-tPA were retrospectively reviewed. Adequacy of informed consent was reviewed by 5 raters: a neurologist and emergency physician who routinely treat stroke, a medical risk management paralegal, a bioethicist, and a lay person. Raters assessed the quality of the informed consent presentation by the treating physician and the degree of understanding demonstrated by the patient/family authorizing consent. Factors associated with adequacy of consent were analyzed. RESULTS: Consent was rated as adequately understood by the patient-family in 78.6% cases. Agreement between all 5 raters with regard to the patient-family understanding of consent was poor and also between the subgroups of non-physician and physician (all k< 0.20). Similarly, the quality of the physician consent process was poor for agreement between all 5 raters (k=0.07) or between the subgroup of the 3 non-physician raters (k=-0.06) and fair between the 2 physician raters (k=0.24). The legal reviewer and the bioethicist rated the physician consent process as being of lower quality than did the two physicians and the layperson. CONCLUSION: Despite high variability in the perception of informed consent among raters in this time-sensitive clinical situation, almost 80% of patients were rated by all reviewers as having adequate understanding of risks and benefits of tPA. This suggests the need for a standardized but brief tPA consent process that includes patient/family demonstration of understanding.